TRANSFORMASI DIGITAL MELALUI INOVASI E-GOVERNMENT PADA PEMERINTAH DAERAH KABUPATEN BUTON SELATAN - Nastia Nastia (Governance, 2024)
The 4.0 and 5.0 era in utilizing technology to improve public services and governance will be a challenge for the government, especially local governments today. Digital transformation for better governance can have an impact on public services, increase citizen engagement, and encourage economic growth. The focus of this research is how digital transformation policies are implemented through the implementation of e-government in the South Buton Regency Regional Government. The observation method is combined with qualitative descriptive analysis. The results show that, compared to other countries, especially in Southeast Asia, Indonesia is still far behind in terms of local government digital transformation. The absence of implementation standardization, inadequate human resources, uneven infrastructure, lack of community involvement, and lack of government commitment are some of the inhibiting factors. The West Java Provincial Government is undergoing digital transformation. One example is the implementation of e-government by the South Buton government. For e-government development to run smoothly, everyone must work together.